Pendampingan Wali Murid Melalui Spiritual Parenting di Madrasah Ibtidaiyah Miftahul Jinan Wonoayu Sidoarjo - Sufinatin Aisida; Moh. Ismail (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
This assistance aims to increase the knowledge and understanding of MI Miftahul Jinan Wonoayu parents in Sidoarjo, through spiritual parenting. The activity was held at MI Miftahaul Jinan Building. Parents have never received assistance related to spiritual parenting activities. Every day parents are busy with routines that cannot be abandoned. The methods used include lectures, questions and answers, discussions and mentoring. The result is a significant change in the knowledge and understanding of parents after the activity is completed.